“Mirror, mirror on the wall [...]” – When the world of fairy tales crosses the boundaries of time and allows the present to be seen in Grimm’s mirror of contemporary caricature - Derecka, Małgorzata (Papers in Linguistics, 2025)
This article examines the combination of words and images in political cartoons based on the famous phrase “Mirror, mirror on the wall [...]” from the Brothers Grimm’s fairy tale about Snow White. The aim of the study is to show how a single playful, fairy-talelike expression is used as a commentary on the political reality of the recent years, and which linguistic and pictorial strategies are used in the process. The article sheds light on the extent to which this iconic fairy tale phrase is used as a linguistic device in caricatures to reflect social and political events and criticise them at the same time. The method of syntactic analysis applied as regards various caricatures made it possible to thoroughly examine the employed stylistic devices, irony and cultural connotations, which reinforce the humour and expressiveness of the caricatures. It was shown that the combination of well-known fairy tale quotations with political themes gives a powerful effect that increases the understanding and relevance of the depiction. The article thus provides new insights into the role of fairy tale language as a critical and creative element of political caricature.